RANCANG BANGUN SISTEM INFORMASI INVENTORY ALAT TULIS KERJA BERBASIS WEB PADA MA SABILUNNAJAH - Puteri Anindya Maulan; Dendy Kurniawan (JURNAL TEKNIK INFORMATIKA DAN MULTIMEDIA, 2022)
The inventory of office stationery must be managed properly by the school or madrasa. This is because office stationery is one of the assessment elements in school or madrasa accreditation. Therefore, the office stationery inventory system in schools must be standardized in accordance with applicable laws and regulations. So far, the current system for inventory of school office stationery at MA Sabilunnajah is still manual or not yet computerized. The result of this research is the Design of a Web-Based Work Stationery Inventory Information System at MA Sabilunnajah which can be used as a medium for inventorying office stationery data so that it can help administrative and school staff effectively and efficiently. This study uses the theme of SMBD (Database Management System) with quantitative methods to process data in the form of numbers for calculating stock of goods and stock of goods in and out. This system only uses a single user, namely as admin for administrative staff. With this inventory system, managing and monitoring inventory and goods in and out of the warehouse will be neater, safer, and more accurate.